Berbagai Faktor Penentu Kesiapan Untuk Berubah Dan Pengaruhnya Terhadap Keberlangsungan Kegiatan UMKM Di Wilayah Terdampak Wabah Covid-19 - Agus Prianto; Ira Kurniawati; Moh. Taufik Wahyudi; Eva Yulistia (UNIVERSITAS PGRI MADIUN, 2020)
Currently, real sector business activities are facing severe challenges. The development of ICT and theemergence of the covid-19 pandemic have led to changes in the business environment. Changes in thebusiness environment require businesses to adjust by developing new business strategies, so that theirbusiness activities are in line with market demands. This study examines various determinants ofreadiness to change and their effect on the continuity of MSME activities in the covid-19 affected areas.The results of the study revealed that the new values and attitudes of micro business operators did notsupport the readiness to change, so they faced the problem of the sustainability of business activities. Newvalues and attitudes are the main factors that shape readiness to change. While the readiness to change isan important factor that determines the sustainability of business activities. In addition, this studyrevealed that the business environment also as a factor forming change readiness and businesscontinuity. This research recommends the importance of strengthening new values and attitudes for,especially for micro business people; so that they are better prepared to face a change. Future studiesneed to examine the effect of sudden environmental changes on the sustainability of business activities.